Simultaneous Synthesis and Rapid Consolidation of Nanocrystalline 3TiAl-Al2O3 Composites by Pulsed Current Activated Heating - Shon, In-Jin; Yoon, Jin-Kook; Hong, Kyung-Tae (AMER SCIENTIFIC PUBLISHERS, 2017)
Nano-powders of Al and TiO were fabricated by high energy ball milling. Nanocrystalline 3TiAl-Al2O3 composite was simultaneously synthesized and consolidated by pulsed current activated sintering within 2 minutes from mechanically milled powders of 3TiO and 5Al. Both hardness and fracture toughness of 3TiAl-Al2O3 composites were higher than that of monolithic TiAl due to addition of hard phase of Al2O3 and crack deflection by Al2O3.
Keywords: MECHANICAL-PROPERTIES; ALLOY